دلالات صدق وثبات الصورة العربية لمقياس الاحتراق النفسي لدى المدرسين - بوفرة, مختار (جامعة الوادي University of Eloued, 2017)
هدفت الدراسة للكشف عن دلالات صدق وثبات مقياس الاحتراق النفسي لدى المدرسين، الذي أعدته كل من ماسلاش وجاكسون،ويتكون المقياس22 بندا موزعة على ثلاث مجالات رئيسة هي: الإجهاد الانفعالي، تبلد المشاعر،نقص الشعور بالانجاز.تكونت عينة الدراسة من 330 مدرس من الابتدائي، متوسط ، ثانوي.تم التحقق من صدق المقياس من خلال:صدق الاتساق الداخلي والصدق التمييزي. كما حسبت مؤشرات ثبات المقياس بطريقة إعادة التطبيق، معادلة ألفا كرونباخ وطريقة التجزئة النصفية. وتوصلت نتائج الدراسة إلى أن جميع قيم معاملات الصدق والثبات كانت مرتفعة ودالة إحصائيا وتدل على صلاحية المقياس. This study aimed to identify the validity and reliability indices of the psychological burnout scale which was prepared originally by Maslach and Jackson. The scale consisted of 22 items distributed on 3 different subscales: emotional exhaustion depersonalization personal accomplishment The study sample consisted of 330 teachers from primary, intermediate and secondary schoolsTo evaluate the validity of scale, several ways were used: the internal consistency and discriminant validityThe reliability of the test was calculated by test-retest Cronbach alpha and split – half methodsThe results of the study showed that the validity and reliability values were high and significant.
مقال
Keywords: دلالات الصدق؛دلالات الثبات؛مقياس الاحتراق النفسي; Validity indices, Reliability indices, psychological burnout scale